Integration of histology, transcriptome and metabolome reveals the effect of cold stress on the liver of cobia (Rachycentron canadum) - Xiaolong Zhao; Yu Li; Qian Ma; Jiansheng Huang; Jiandong Zhang; Gang Chen (Aquaculture Reports)
Cobia (Rachycentron canadum) is ideal for marine cage culture in the South China Sea. To investigate its response to cold stress, histological, transcriptomic, and metabolomic analyses of the liver were conducted. Fish were subjected to cold stress at 18 °C, and liver samples were collected at three sampling time points under cold stress (0, 4, and 7 days). Histological examination of the liver revealed cytoplasm vacuolization of the hepatocytes and accumulation of lipid droplets under cold stress. In addition, the microRNA (miRNA) and mRNA expression profiles in the liver were examined using the Illumina Novaseq 6000 platform. As a result, a total of 90 differentially expressed (DE) miRNAs and 86 predicted target genes were identified, among which 6 miRNAs and 43 target genes exhibited significantly clustered changing trends. Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis of these genes showed that they were significantly enriched in galactose metabolism and amino sugar and nucleotide sugar metabolism pathways. The weighted gene co-expression network analysis (WGCNA) of the differentially expressed genes (DEGs) revealed three modules that were significantly correlated with cold stress. KEGG analysis of the genes within these modules showed significant enrichment in eight metabolism-related pathways (including Steroid biosynthesis, Glutathione metabolism, etc.) and 20 other terms. Furthermore, a total of 280 significantly regulated metabolites (SRMs) were identified using an LC-ESI-MS/MS system. An integrative transcriptome and metabolome analysis suggested that the DEGs and SRMs were significantly enriched in glycerophospholipid metabolism and biosynthesis of amino acids pathways. The genes and metabolites identified in this study might play an important role in the regulation of the cold stress response of cobia, and the investigation could provide new insights into the molecular mechanisms underlying the adaptation of teleost species to climate change.